1982
DOI: 10.1161/01.atv.2.6.523
|View full text |Cite
|
Sign up to set email alerts
|

Relationships of nutrient intake to lipids and lipoproteins in 1234 white children. The Lipid Research Clinics Prevalence Study.

Abstract: Using the geographically and socioeconomjcally varied collaborative Lipid Research Clinics Prevalence Study data, this report focuses upon relationships between dietary intake and plasma lipids and lipoproteins in 1234 white children, 661 boys and 573 girls, aged 6-19 years who were sampled in a random recall (Visit 2) from large populations in six Lipid Research Clinics. Using multiple regression analysis, we found that in 6-to 12-year-old boys the dietary polyunsaturated-to-saturated fat ratio was inversely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
1

Year Published

1982
1982
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 52 publications
(30 reference statements)
1
22
0
1
Order By: Relevance
“…However, none of the human studies have taken into account the current diet of the subjects, parental hypercholesterolemia or when performed in children, the pubertal status. These factors are all associated with plasma cholesterol concentration in children (Berenson et al, 1981;Glueck et al, 1982;Morrison et al, 1980) and are potential confounders of relationship. As part of the Fleurbaix Laventie Ville Sante  study, data were available for 474 prepubertal children aged 5 ± 11 y for whom informations on infant diet have been collected.…”
Section: Introductionmentioning
confidence: 99%
“…However, none of the human studies have taken into account the current diet of the subjects, parental hypercholesterolemia or when performed in children, the pubertal status. These factors are all associated with plasma cholesterol concentration in children (Berenson et al, 1981;Glueck et al, 1982;Morrison et al, 1980) and are potential confounders of relationship. As part of the Fleurbaix Laventie Ville Sante  study, data were available for 474 prepubertal children aged 5 ± 11 y for whom informations on infant diet have been collected.…”
Section: Introductionmentioning
confidence: 99%
“…While this difference between boys and girls is intriguing, it needs to be con®rmed by other studies. Differences in the relationship between diet and blood lipid concentrations between the sexes have been shown in several other studies in adults (Gordon et al, 1982;Ness et al, 1996;Frost et al, 1999), adolescents and children (Glueck et al, 1982;Boreham et al, 1999) and babies (Simell et al, 1999). In the STRIP study the authors found an intervention diet which lowered saturated fat and cholesterol intake relative to a control group only achieved a signi®cant reduction in total cholesterol levels in boys Ð a ®nding which is in line with our own Ð however, this may have been attributable to the fact that saturated fat and cholesterol intakes by girls were higher than those by boys throughout the trial, while the P:S ratio of their diet was lower (Niinikoski et al, 1996).…”
Section: Discussionmentioning
confidence: 75%
“…We may also speculate that African American families maintained a more stable household environment throughout life, or that children were more likely to recreate aspects of their childhood households, such as diet, when they become adults. At the Princeton LRC visit, parent-child correlations for carbohydrate intake were higher among black families than white families ( 46 ), with nutrient intake having a small but signifi cant association with plasma lipids in this cohort (47)(48)(49). However, to our knowledge, longitudinal data to support this supposition are lacking.…”
Section: Discussionmentioning
confidence: 94%